2018
DOI: 10.1038/s41467-017-02753-0
|View full text |Cite
|
Sign up to set email alerts
|

Closed-loop stimulation of temporal cortex rescues functional networks and improves memory

Abstract: Memory failures are frustrating and often the result of ineffective encoding. One approach to improving memory outcomes is through direct modulation of brain activity with electrical stimulation. Previous efforts, however, have reported inconsistent effects when using open-loop stimulation and often target the hippocampus and medial temporal lobes. Here we use a closed-loop system to monitor and decode neural activity from direct brain recordings in humans. We apply targeted stimulation to lateral temporal cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
220
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 280 publications
(254 citation statements)
references
References 55 publications
(56 reference statements)
12
220
1
Order By: Relevance
“…These results, therefore, could provide an informed basis for the use of intermittent and targeted neuromodulation to aid individuals experiencing severe emotion dysregulation at both extremes of the spectrum. Indeed, this approach, applied to other domains and across cognitive and emotional tasks, could allow us to arrive at a more refined view of how to use neural stimulation to therapeutically alter the circuitry underlying important domains of functioning, such as maladaptive emotional processing and decision making, with implications for a wide array of neuropsychiatric diseases (33,34,51,52).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These results, therefore, could provide an informed basis for the use of intermittent and targeted neuromodulation to aid individuals experiencing severe emotion dysregulation at both extremes of the spectrum. Indeed, this approach, applied to other domains and across cognitive and emotional tasks, could allow us to arrive at a more refined view of how to use neural stimulation to therapeutically alter the circuitry underlying important domains of functioning, such as maladaptive emotional processing and decision making, with implications for a wide array of neuropsychiatric diseases (33,34,51,52).…”
Section: Resultsmentioning
confidence: 99%
“…Second, after establishing a subset of behavioral models which were high-performing, in separate task sessions, we tested whether identified hidden states within these behavioral state space models can be driven by stimulation in specific brain networks. We hypothesized that direct electrical intracranial stimulation in different brain regions would have differential, and causal, effects on these behavioral features as has been hinted at with stimulation in other brain regions in learning and memory (50,51), mood (35,52), and OCD (36,53,54). As a final test, we used the state-space model in closed-loop adaptive stimulation to modulate behavior predictably.…”
Section: Introductionmentioning
confidence: 99%
“…In the first study of its kind, applying an integrated IEEG-fMRI method, we have shown that established markers of memory encoding correspond to meaningful network differences captured by rsfMRI. In clinical terms, knowing a region is a hub, playing an important role in multi-regional and multi-functional connectivity, may inform technologies trying to identify the most effective targets to electrically or pharmacologically stimulate for cognitive enhancement in areas such as memory Ezzyat Y et al, 2018;Kucewicz MT et al, 2018), or perhaps be used to identify the areas with sufficient influence over targets to generate effective neuro-feedback loops (Hohenfeld C et al, 2017;Murphy AC et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…To benchmark our MSV findings we conducted parallel analyses of wavelet-derived spectral power at frequencies ranging between 3-180 Hz. To aggregate across MTL electrodes within each subject we applied an L2-penalized logistic regression classifier using features extracted during the encoding period to predict subsequent memory performance (Ezzyat et al, 2017(Ezzyat et al, , 2018. To estimate the generalization of the classifier, we utilized a nested cross-validation procedure in which we trained the model on N − 1 sessions using the optimal penalty parameter selected via another inner cross-validation procedure on the same training data (see Appendix 4.6 for details).…”
Section: Classification Of Subsequent Memory Recallmentioning
confidence: 99%